Nursing students’ attitudes on caring for people living with HIV/AIDS. A European Multicentre Study: Nursing students’ attitudes and HIV - Bonacaro, Antonio; Stroumpouki , Theodora; Triglia, Carmela; Vizilio , Emanuele; Stavropoulou , Areti; Papageorgiou, Dimitrios; Rubbi , Ivan (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Caring for people with HIV/AIDS is a challenging issue for nursing students, involving sometimes misconceptions due to different cultural, political and religious views. The aim of this project was to investigate nursing students’ attitudes on caring for people with HIV/AIDS.Methods: A convenient sample of undergraduate nursing students enrolled in four European universities was recruited. Data were collected by administering the AIDS Attitude Scale (AAS). Statistical analysis included the ANOVA test, the t–test for independent variables, and the Kruskal-Wallis test with a confidence level P